2013
DOI: 10.1074/jbc.c113.511261
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Protein Deacetylase SIRT6 by Long-chain Fatty Acids and Widespread Deacylation by Mammalian Sirtuins

Abstract: Background: Sirtuins regulate metabolism, genome maintenance, and stress responses. Results: Long-chain free fatty acids stimulate SIRT6 deacetylase, and sirtuins display distinct but overlapping specificity for diverse acylated peptides. Conclusion: SIRT6 is activated by biologically relevant fatty acids, and long-chain deacylation is a general feature of sirtuins. Significance: Discovery of endogenous, small-molecule activators of SIRT6 demonstrates the therapeutic potential of compounds that promote SIRT6 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
728
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(760 citation statements)
references
References 36 publications
28
728
3
1
Order By: Relevance
“…In marked contrast to its role in energy metabolism, the involvement of NAD + in these enzymatic reactions is based on its ability to function as a donor of ADP-ribose, a reaction that, if sustained, can lead to the depletion of the intracellular NAD + pool. [1][2][3][4][5] The pro-survival role of NAD + has been particularly well described in cells exposed to genotoxic/oxidative stress. In response to DNA damage, PARP1, the founding and most abundant member of the PARP family, binds to DNA strand breaks and initiates a repair response by catalyzing the posttranslational modification of several nuclear proteins, including itself.…”
mentioning
confidence: 99%
“…In marked contrast to its role in energy metabolism, the involvement of NAD + in these enzymatic reactions is based on its ability to function as a donor of ADP-ribose, a reaction that, if sustained, can lead to the depletion of the intracellular NAD + pool. [1][2][3][4][5] The pro-survival role of NAD + has been particularly well described in cells exposed to genotoxic/oxidative stress. In response to DNA damage, PARP1, the founding and most abundant member of the PARP family, binds to DNA strand breaks and initiates a repair response by catalyzing the posttranslational modification of several nuclear proteins, including itself.…”
mentioning
confidence: 99%
“…Finally, 20 hit compounds ( Figure 1) were selected for subsequent biochemical test; to the best of our knowledge, all of these compounds have not been reported as sirtuin inhibitors so far. The predicted binding modes of the selected compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are shown in Figure 1. We observed that although these compounds may have different binding modes with SIRT5, all of them are likely to form hydrogen-bonding/electrostatic interactions with Tyr102 and Arg105 (Figure 1).…”
Section: Customized Virtual Screeningmentioning
confidence: 99%
“…[7][8][9] SIRT4 can remove lipoic acid and biotin residues from active site lysines both in vitro and in vivo, [10] while SIRT1-3 seem to be decrotonylases. [6,8] Owing to the multifaceted activity on various substrate proteins, sirtuins are implicated in many biological processes such as metabolic regulation, transcriptional regulation, genome stability, and cell survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 Specifically, SIRT6 is also activated by fatty acids, providing additional metabolite integration. 70 Together, these studies suggest that altered glucocorticoid rhythms, feeding patterns, and food type may contribute to functional desynchrony between the master pacemaker and the liver.…”
mentioning
confidence: 99%